2022
DOI: 10.1038/s41564-022-01126-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression broadens evolutionary pathways to drug resistance and treatment failure during Acinetobacter baumannii pneumonia in mice

Abstract: Acinetobacter baumannii is increasingly refractory to antibiotic treatment in healthcare settings. As is true of most human pathogens, the genetic path to antimicrobial resistance (AMR) and the role that the immune system plays in modulating AMR during disease are poorly understood. Here we reproduced several routes to fluoroquinolone resistance, performing evolution experiments using sequential lung infections in mice that are replete with or depleted of neutrophils, providing two key insights into the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 82 publications
1
21
0
Order By: Relevance
“…Censoring was not required as all study participants were followed up until death or 30 days. We used STATA 16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Censoring was not required as all study participants were followed up until death or 30 days. We used STATA 16…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients in C2 with CRKp had new risk factors, including chronic liver disease and recent surgery. Recent data support severe immunosuppression, including neutropenia, to promote antimicrobial resistance [16][17][18]. Significant antibiotic pressure in these patients and immunosuppression promotes the survival of persistent bacteria, enabling the development of multidrug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Second, azoles were still widely used in clinical treatment of fungal infections and as prophylaxis for highrisk populations (Vardakas et al, 2006;Hicheri et al, 2012;Coussement et al, 2021). Previous study indicated that immunosuppression coupled with antimicrobial stress could result in rapid selection of resistance and expansion of antimicrobialresistant populations in the respiratory tract (Huo et al, 2022). Fluconazole is primarily renal cleared and has high urinary concentration (Lazar and Wilner, 1990), which could become a selective pressure for resistant isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, persisters constitute a viable pool that facilitates resistance development by prolonging the presence of viable bacteria during antibiotic treatment ( 26 , 27 ), but various other mechanisms have been suggested ( 6 , 8 , 10 , 26 , 28 ). For example, Windels et al and Huo et al identified that the increased mutation rate in highly persistent strains promotes evolution toward antibiotic resistance ( 6 , 29 ), and Levin-Reisman et al indicated the role of epistasis between antibiotic persistence and resistance mutations ( 28 ).…”
Section: Introductionmentioning
confidence: 99%